Foliar Fungal Endophytes of Selected Medicinal Plants from the Province of Albay, Philippines - Guerrero, Jonathan Jaime G.; General, Mheljor A.; Imperial, Jazzlyn T. (Science Diliman: A Journal of Pure and Applied Sciences, 2019)
Fungal endophytes were isolated from the leaves of the 10 most frequently used medicinal plants in the province of Albay, Philippines at three different locations: upland, lowland, and coastal areas. Their occurrence, frequency, and isolation rates were compared. A total of 120 isolates belonging to 17 species were identified. Glomerella cingulata (Stoneman) Spauld. & H. Schrenk and Colletotrichum gloeosporioides M.B. Dickman were the most frequent fungi occurring in 10 and nine plants, respectively. No significant difference in the total number of isolates, as well as the total number of unique species from among sampling sites, was detected. Blumea balsamifera (L.) DC harbored the most endophytes with 16 isolates, while banana leaves yielded the least with eight isolates. There were species of fungi that cut across all sampling sites, while a few occurred only in one site. The collection of additional samples from other sites within the province and the testing of the biological properties of the isolates are recommended. Keywords : Albay, endophytes, Glomerella cingulata, medicinal plants, upland